Is PROMIS the new standard for patient-reported outcomes measures in orthopaedic trauma research?. (May 2020) - O'Hara, Nathan N; Richards, John T.; Overmann, Archie; Slobogean, Gerard P.; Klazinga, Niek S.
Highlights: This review describes the unique elements of the PROMIS architecture. The study compares the frequency for which PROMIS measures are used in recent orthopaedic trauma literature compared to other common patient-reported outcome measures. We suggest some possible barriers to a broader adoption of PROMIS in orthopaedic trauma research. Abstract: This review describes some of the benefits of the Patient-Reported Outcomes Measurement Information System (PROMIS) architecture, determined how frequently PROMIS measures were used in the current orthopaedic trauma literature, and compared the features of PROMIS instruments with other frequently used patient-reported outcomes measures (PROMs). PROMIS instruments have several unique elements to their architecture, such as item response theory, computerized adaptive testing options, and scaling using T-scores, that differentiate the instruments from many other PROMs. Over the past five years, 108 different PROMs were reported in 319 studies published in high-impact orthopaedic journals. PROMIS measures, including PROMIS Physical Function, Pain Interference, and Upper Extremity Function, were only used in seven studies (2%). PROMIS measures were found to be comparable to other more common PROMs with respect to respondent burden, administration options, and psychometric assessments specific to fracture patients. Likely, the limited familiarity and interpretability of PROMIS measures in the fracture population remain the most substantial barriers to broader adoption in orthopaedic trauma research.